Methodological approaches to quality management in construction: inclusion, digitalization, safety - Filippov, Oleksandr (Ways to Improve Construction Efficiency, 2023)
The article examines modern methodological approaches to quality management in construction, which reflect new requirements for design, engineering and management processes in a dynamic socio-economic environment. The focus is on three key dimensions of quality: inclusiveness, digitalization and safety. The integration of these components into the quality management system is considered as a necessary condition for the effective functioning of the construction industry in the 21st century. The concept of quality is described, which goes beyond the technical characteristics of construction products and covers social impact, accessibility, environmental sustainability and safety aspects at all stages of the object's life cycle. An analysis of modern approaches to the implementation of inclusive design in construction is carried out, which allows taking into account the needs of people with disabilities, low-mobility groups, the elderly, children and internally displaced persons. It is determined that inclusiveness is not only an ethical but also an economically feasible factor in the formation of a high-quality urban environment. Digitalization is considered as a driving force for improving the quality of construction: the possibilities of using BIM modeling, digital building passports, automated quality control systems, IoT technologies for monitoring the technical condition of structures are revealed. It is noted that digital technologies significantly improve communication between participants in the construction process, reduce the number of errors, improve risk forecasting and accelerate the adoption of management decisions. Safety is defined as a multi-level category that covers both physical safety (fire, structural, environmental) and social, which includes comfort, psychological security and social justice. The regulatory and legal framework of Ukraine in the field of construction safety is analyzed, in particular in the context of European integration processes and adaptation to EU standards. The article proposes an integrated quality management model based on a systemic approach, the use of key performance indicators (KPI), the implementation of international ISO standards and adherence to the principles of sustainable development. The need to combine state regulation with the innovative potential of the private sector, in particular through public-private partnership mechanisms, is argued. The results of the study have significant scientific and applied potential for updating the methodological principles of quality management in construction and can be used in the development of policies in the field of urban planning, construction regulation and educational programs for training a new generation of specialists.